(untitled) (Journal of Imam Al-Kadhim College, 2023)
Investigating ambiguity in political statements is the goal of the current study. More adequately, it clarifies the lexical and structural ambiguities that are used by Vince Cable as a member of the British Liberal Democrats in 2018. The importance of this speech lies in the fact that it discusses the Brexit argument which is about the issue of leaving the European Union for Britain. Moreover, it presents some other crucial issues like racism, immigration, and economy. This paper provides a theoretical background on ambiguity and its relavant types. Two methods are chosen for analysing the data: descriptive (analysing the data descriptively) and statistical (analysing the data statistically by using frequencies and percentages). It is found that the speaker employs lexical ambiguity more than he does with structural ambiguity with percentages that amount to (75%) and (25%), respectively. It is concluded that lexical ambiguity is more appropriate for achieving linguistic ambiguity than structural one.